PENGARUH PEMBERIAN CUKA APEL (Malus sylvestris Mill) VARIETAS MANALAGI TERHADAP KADAR TRIGLISERIDA DARAH TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIBERI DIET TINGGI LEMAK DAN DIINDUKSI ALOKSAN - Yuliyanti Yuliyanti; A. Sareh Arjono Tjandra; Herin Setianingsih (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
Hypertriglyceridemia is one of the risk factors for cardiovascular disease and acute pancreatitis (Pejic and Lee, 2006; Brahm and Hegele, 2013; Afari et al., 2015). One way to treat it by using the apple vinegar (Malus sylvestris Mill) of manalagi varieties which contained high antioxidants and acetic acid as well as more durable than the fresh fruit. The study aimed to know the effect of the Apple vinegar of manalagi varieties (Malus sylvestris Mill) to blood triglyceride levels of white male rats (Rattus norvegicus) wistar strain with high-fat diet and induced by alloxan. The study used the post test only control group design, with 24 rats samples which were divided into three groups. The negative control group (K0) only received standard diet for 24 days, the positive control group (K1) received a high-fat diet for 7 days and induced by alloxan with doses of 90 mg/kgBW of rats, and treatment group (K2) was given a high-fat diet for 7 days, induced by alloxan and received the apple vinegar (Malus sylvestris Mill) of manalagi varieties with a dose of 0,27 ml/100 g BW of rats for 14 days. The results by using one way ANOVA showed the significance value of the data p = 0,974 (p>0,05) so that there is no significant difference of the mean of blood triglycerides levels between K0, K1 and K2. This study concluded that apple vinegar (Malus sylvestris Mill) of manalagi varieties can not significantly lower the blood triglyceride levels of white male rats (Rattus norvegicus) wistar strain with high-fat diet and induced by alloxan. Further study about apple vinegar of manalagi varieties is required to define its effects. Â Keywordsâ€”: High-Fat Diet, Alloxan, Triglyceride, Apple Vinegar (Malus sylvestris Mill) of Manalagi Varieties